"Sometimes I feel like they look at me the same way I were an alien": Experiences of refugee women in a small town in Iceland (Translated by webmaster) - Skaptadóttir, Unnur Dís; Kristjánsdóttir, Erla S. (School of Social Sciences, 2017)
The study discussed in this article examines the experiences of a small group of women who came to Iceland as quota refugees. They had been forced to leave their homes and had lived in refugee camps, before they were resettled in a small town in Iceland. Semi-structured interviews were conducted to explore their lived experiences of adaptation of integration in their new home, after experiencing years of hardship in country of origin. Four main themes emerged from this study: Receptivity of receiving society, learning Icelandic, gender roles here and there and social ties. The main results indicate that the integration process was difficult; that communication between the women and natives was limited and that the natives did not show much interest in getting to know the women. A more detailed analysis revealed that although the women had found security in the town and had become friends with other refugees and a few other individuals, which made them feel a sense of belonging, they felt isolated from Icelandic society. Rannsóknin sem þessi grein byggir á fjallar um reynslu og upplifun flóttakvenna sem voru nauðbeygðar til að yfirgefa heimili sín, búa í flóttamannabúðum og flytja í lítið bæjarfélag á Íslandi. Rannsóknin varpar ljósi á hvernig konurnar upplifðu sig eftir miklar hremmingar í eigin landi, velgengni þeirra og erfiðleika við að hefja nýtt líf á Íslandi. Tekin voru hálfopin viðtöl til að skoða reynslu þessara flóttakvenna og upplifun þeirra af því að aðlagast nýju landi. Fjögur þemu spruttu upp úr gögnunum: Móttækileiki nærsamfélagsins, að læra íslensku, kynjahlutverk hér og þar og félagsleg tengsl. Helstu niðurstöður eru að aðlögun kvennanna að samfélaginu var erfið þar sem samskiptin milli þeirra og innfæddra voru takmörkuð og konunum fannst lítill áhugi meðal innfæddra á að kynnast þeim. Nánari greining á þessum þemum leiddi í ljós að þrátt fyrir að hafa fundið öryggi í bæjarfélaginu og myndað þar tengsl við aðrar flóttakonur auk nokkurra annarra einstaklinga, sem gerði þeim kleift að líða eins ...